Problem Solving Ability of Remboken 1 Middle School Students in Solving Story Problems in Algebraic Form Based on Polya's Steps - Katuuk, Rivaldo Chun; Sumarauw, Sylvia J. A.; Pulukadang, Rosiah J. (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Problem-solving abilities are essential for the development of students' mathematical abilities. This ability must be described clearly to contribute to problem-solving and mathematical problem-solving abilities. This research aimed to describe problem-solving abilities in solving algebraic story problems based on Polya's steps: understanding the problem, formulating a plan, implementing the problem, and checking again. The subjects in this research were three students selected from 12 students in class VII-C at SMP Negeri 1 Remboken, consisting of students with high, medium and low abilities based on the mathematical problem-solving ability test results. The data collection techniques used were through written tests, interviews and documentation. The results of the research that has been explained show that problem-solving abilities in solving questions are divided into three categories, namely high, medium and low. Students with high-category abilities can master 4 Polya steps with up to 5 questions. Students with the medium ability category can master 4 Polya steps for questions number 2, 4 and 5, master 3 of the 4 Polya steps, namely steps 1, 2 and 3 for question number 1, and can master 2 of the 4 Polya steps, namely step 1 and 2. Meanwhile, students with low ability categories can master the 4 Polya steps only in question number 1, master 2 of the 4 Polya steps, namely steps 1 and 2 for question number 2, and questions number 3, 4 and 5 for subjects with low ability do not able to do it